2007
DOI: 10.1016/j.cardiores.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent activation of bradykinin B2 receptors and mitochondrial KATP channels trigger cardiac postconditioning through redox signaling

Abstract: Intermittent targeting of specific cellular sites (i.e. BK B2 receptors and mK(ATP) channels) during early reperfusion triggers PostC protection via ROS signaling. Since neither intermittent oxygenation nor exogenous ROS generators can trigger protection, it is likely that intermittent autacoid accumulation and ROS compartmentalization may play a pivotal role in PostC-triggering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
169
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(185 citation statements)
references
References 49 publications
11
169
1
4
Order By: Relevance
“…This supports the idea that the delayed recovery of intracellular pH during initial reperfusion, is mandatory to limit infarct size in PostC mainly via prevention of mPTP opening and prevention of RIRR [8,9,17,29,30,34,55]. Both in vitro and in vivo studies demonstrated that large spectrum ROSscavengers such as N-acetyl-L-cysteine (NAC) and/or N-(2-mercaptopropionyl)-glycine (MPG) given either during the PostC maneuvers [8,51,54,63] or during AB infusion [8,9,10,13] prevented their protective effects [13,51,54,63]. Moreover, addition of alkaline buffer in early reperfusion abolishes both AB-and PostC-protection [8,9,17,29,55].…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…This supports the idea that the delayed recovery of intracellular pH during initial reperfusion, is mandatory to limit infarct size in PostC mainly via prevention of mPTP opening and prevention of RIRR [8,9,17,29,30,34,55]. Both in vitro and in vivo studies demonstrated that large spectrum ROSscavengers such as N-acetyl-L-cysteine (NAC) and/or N-(2-mercaptopropionyl)-glycine (MPG) given either during the PostC maneuvers [8,51,54,63] or during AB infusion [8,9,10,13] prevented their protective effects [13,51,54,63]. Moreover, addition of alkaline buffer in early reperfusion abolishes both AB-and PostC-protection [8,9,17,29,55].…”
Section: Introductionsupporting
confidence: 63%
“…However, we have been unable to reproduce cardioprotection with ROS generator given during early reperfusion [51]. Since ROS-scavengers (NAC or MPG) abolished AB-and PostC-induced protection [8,9,51,54,63], it is likely that the type, the concentration, and/or the compartmentalization of ROS/RNS may play a pivotal role in triggering protection at early reperfusion time.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations